GENDER OF ACRONYMS IN CONTEMPORARY SLOVENIAN (Philological Studies, 2019)
The paper presents results of a corpus analysis of 40 most frequent acronyms in contemporary Slovenian that was performed using the Gigafida 2.0 corpus. The aim of the analysis was to study the gender and morphological behaviour of most frequent Slovenian acronyms. Results of the study are compared with the data from the Slovenian Normative Guide (2001).
Keywords: acronyms, grammar, morphological description, corpus analysis, Slovenian